The prediction models for postoperative overall survival and disease‐free survival in patients with breast cancer. (24th May 2017) - Shigemizu, Daichi; Iwase, Takuji; Yoshimoto, Masataka; Suzuki, Yasuyo; Miya, Fuyuki; Boroevich, Keith A; Katagiri, Toyomasa; Zembutsu, Hitoshi; Tsunoda, Tatsuhiko
Abstract: The goal of this study is to establish a method for predicting overall survival (OS) and disease‐free survival (DFS) in breast cancer patients after surgical operation. The gene expression profiles of cancer tissues from the patients, who underwent complete surgical resection of breast cancer and were subsequently monitored for postoperative survival, were analyzed using cDNA microarrays. We detected seven and three probes/genes associated with the postoperative OS and DFS, respectively, from our discovery cohort data. By incorporating these genes associated with the postoperative survival into MammaPrint genes, often used to predict prognosis of patients with early‐stage breast cancer, we constructed postoperative OS and DFS prediction models from the discovery cohort data using a Cox proportional hazard model. The predictive ability of the models was evaluated in another independent cohort using Kaplan–Meier (KM) curves and the area under the receiver operating characteristic curve (AUC). The KM curves showed a statistically significant difference between the predicted high‐ and low‐risk groups in both OS (log‐rank trend test P  = 0.0033) and DFS (log‐rank trend test P  = 0.00030). The models also achieved high AUC scores of 0.71 in OS and of 0.60 in DFS. Furthermore, our models had improved KM curves when compared to the models using MammaPrint genes (OS: P  = 0.0058, DFS: P  = 0.00054). Similar results were observed when our model was tested in publicly available datasets. These observations indicate that there is still room for improvement in the current methods of predicting postoperative OS and DFS in breast cancer. Abstract : This study reports an analysis of prediction models for postoperative overall survival (OS) and disease‐free survival (DFS) in patients with breast cancer, in which we incorporated genes we found associated with the postoperative survival into MammaPrint genes, often used to predict prognosis of patients with early‐stage breast cancer, and constructed postoperative OS and DFS prediction models using a Cox proportional hazard model. Not only did our models achieve an area of a receiver operating characteristic curve (AUC) of 0.71 and 0.60 on an independent test set, but the KM curves also showed a statistically significant difference between the predicted high‐ and low‐risk groups in both OS (log‐rank trend test P  = 0.0033) and DFS (log‐rank trend test P  = 0.00030).